Scientific and technological investigation of the protective effect of rutin on intestinal mucositis induced by 5-fluorouracil (Research, Society and Development, 2021)
Chemotherapy is one of the main oncological treatments, in which it has several side effects, including mucositis. Rutin belongs to the class of flavonoids and has clinically relevant functions, potentially beneficial in preventing diseases and antioxidant activity. Therefore, the objective of this study was to carry out scientific and technological monitoring of the pharmacological properties of rutin and its relationship as a possible therapeutic agent in the control of intestinal mucositis. Monitoring was carried out through the Science direct and Web of Science bases, and technological bases, the European Patent Institute and the National Intellectual Property Institute. The descriptors were: "Rutin, Rutin" and "ulcer, Rutin" and "biological activity", "Rutin and pharmacology" and "Rutin and cancer". The searches were carried out in October 2019, being considered publications from the last 10 years. It can be seen that there has been an increase in studies related to rutin in the last decade, highlighting several pharmacological activities of the compound.